School Social Work in Vietnam: Development and Capacity Building through International Collaboration - Leticia Villarreal Sosa; Nguyen Thu Ha (International Journal of School Social Work, 2020)
International collaborations and exchanges have been a part of the social work profession since its beginning. The internationalization of social work is firmly established with the presence of multiple international social work organizations. In the specialization of school social work, there are opportunities for exchange through an international school social work conference held every two to three years. It was at this conference that the authors met to initiate a collaboration in support of the development of school social work in Vietnam. This paper discusses the collaborative efforts and project funded by a Fulbright Specialist grant to support the development of school social work in Vietnam. The professional development seminars provided opportunities for a deeper understanding of the role of the school social worker in psychosocial assessment, needs assessment, addressing issues such as bullying, mental health challenges, suicidality, multi-tiered systems of support, and the evidence based process. As a still evolving specialization, school social work would benefit from continued international collaborations and building opportunities for intellectual and professional exchanges.
Keywords: school social work; Vietnam; international collaboration; Fulbright Specialist